Navigating the complexity of chronic HIV-1 associated immune dysregulation. (June 2022) - Boyd, Mollie AA; van Bockel, David; Munier, Cynthia Mee Ling; Kelleher, Anthony D
Abstract : Despite successful viral suppression with antiretroviral therapy, chronic HIV-1 infection is associated with ongoing immune dysfunction. Investigation of the complex immune response in treated and untreated individuals with chronic HIV-1 infection is warranted. Immune alterations such as monocyte phenotype and Th-17/Treg ratios often persist years after the reduction in viraemia and predispose many individuals to long-term comorbidities such as cardiovascular disease or cancer. Furthermore, while there has been extensive research on the latent reservoir of treated patients with chronic HIV-1, which prevents the discontinuation of treatment, the mechanism behind this remains elusive and needs further investigation. In this review, we assist in navigating the recent research on these groups of individuals and provide a basis for further investigation.